Health-related quality of life in children with presumptive TB - M.G. Anthony; L.S. Johnson; M. van Niekerk; A. Mfwaze; B. Bavuma; A.C. Hesseling; G. Hoddinott; M.M. van der Zalm (IJTLD Open)
BACKGROUND: Respiratory illnesses, including pulmonary TB (PTB), cause significant morbidity. We aimed to understand the health-related quality of life (HRQoL) of children with presumptive PTB. METHODS: Children aged 0–13 years presenting with presumptive PTB were enrolled. This study includes children who started TB treatment and children in whom TB was excluded (symptomatic controls). Quantitative data were collected using the Toddler and Infant quality of life Instrument (TANDI) (<3 years) and European Quality of Life-5 Dimensions-Youth (EQ-5D-Y) (>3 years) measures. Qualitative data were collected through in-depth interviews using thematic analysis. RESULTS: Quantitative data from caregivers of 201 children (TANDI: n = 170; EQ-5D-Y: n = 31) showed 77 (38.3%) were diagnosed with TB, while 124 (61.7%) were symptomatic controls. Qualitative data from 15 caregivers of 21 children included 10 (67%) children with TB and 5 (33%) symptomatic controls. The median TANDI Visual Analogue Score (VAS) for overall health was 90% (IQR 80–100); the EQ-5D-Y VAS median was 95% (IQR 80–100). Caregivers described decreased energy, difficulty eating, and increased sleep using qualitative interviews, which were not reflected in the quantitative data. No differences were found between children with TB and symptomatic controls. CONCLUSIONS: HRQoL was high in children with TB, but discrepancies between quantitative and qualitative measures highlight the limitations of the current HRQoL measures.